The mobility of metals in acid mine drainage from abandoned coal mines - Halbich, Torsten Franz Joachim (Department of Geological Sciences, 2023)
The acid mine-drainage contaminated Blesbokspruit catchment west of Witbank in Mpumalanga province, South Africa has been investigated, by analysis of its waters, sediments, precipitates and algae, to obtain an understanding of the processes which control the mobility of metals in these waters. The Blesbokspruit drains acid mine drainage originating in surrounding, abandoned coal mine workings. The upper Blesbokspruit (approximately 8 km) including the stream origin, AMD outwelling points, downstream AMD retention ponds and a small wetland were selected for this study. Water, sediment, precipitate, and algae samples were collected from the Blesbokspruit. The water quality of the catchment was determined and compared to mineralogical and major and trace element analyses of sediments, precipitates, and algae. The pH and total dissolved solids of the catchment waters ranged from pH 2.6 to 7.4 and 147 to 3071 mg/ t, respectively. Associated precipitates consisted primarily of jarosite with minor amounts of goethite, lepidocrocite, ferrihydrite and gypsum, with ferrihydrite being the major component of only one precipitate sample. The presence of algae at one of the sampling sites appeared to act as a template for the precipitation of ferrihydrite in a low pH and high acidity environment. Speciation modelling of the Blesbokspruit waters indicated waters saturated with respect to jarosite, goethite, and quartz, in equilibrium with jurbanite, alunite and gypsum, and undersaturated with respect to ferrihydrite and kaolinite. The mobility of iron in the sulphate rich Blesbokspruit waters appeared to be controlled by pyrite oxidation and the solubility of the basic iron sulphate mineral jarosite. In contrast Al mobility appeared to be influenced by different mechanisms. Acidity of the Blesbokspruit waters correlated well (r = 0.942) with Al concentrations in the waters. Dissolved Al correlated with dissolved silica (r = 0.757) in the Blesbokspruit waters and exchangeable acidity correlated with exchangeable Al (r = 0.761) in the associated sediments. The data suggested that Al behaved conservatively in the pH < 4 Blesbokspruit waters and that Al solubility is controlled by dissolution of clay minerals and adsorption to organic matter in the sediments. Although precipitates contain trace elements, precipitation does not have a major effect on the concentration of trace elements in the associated low pH waters. Trace elements were, however, accumulated in the sediments of the Blesbokspruit streambed and the wetland. The wetland acts as a sink for dissolved Na, Ca, Mg, Fe, Mn, Zn, Ni, Pb U, Cu and Co. The mobility of these elements appeared to be controlled by the dissolution of minerals containing these elements and adsorption to organic matter in the wetland and streambed sediments. Not all metals were, however, completely immobilised, and toxic concentrations of Pb (1.3 mg/ t) and elevated concentrations of Al (40 mg/ t ), Fe (1.6 mg/t) and Mn (6.5 mg/t) remained in the water downstream of the wetland.